Vitamin D deficiency, impaired lung function and total and respiratory mortality in a cohort of older men: cross-sectional and prospective findings from The British Regional Heart Study - Olia Papacosta; Peter Whincup; S Goya Wannamethee; Lucy Lennon (BMJ Open)
Objectives Vitamin D deficiency is associated with chronic obstructive pulmonary disease (COPD). We examined the cross-sectional association between 25-hydroxyvitamin D (25(OH)D) and lung function impairment and assessed whether vitamin D deficiency is related to long-term mortality in those with impaired lung function.Design Prospective studySetting General practices in the UK.Participants 3575 men aged 60–79 years with no prevalent heart failure.Outcome measures Airway obstruction and mortality. The Global Initiative on Obstructive Lung diseases (GOLD) spirometry criteria was used to define airway obstruction.Results During the follow-up period of 20 years, there were 2327 deaths (114 COPD deaths). Vitamin D deficiency was defined as serum 25(OH)D levels<10 ng/mL; insufficiency as 25(OH)D 10–19 ng/mL; sufficient as 25(OH)D>20 ng/mL. In cross-sectional analysis, vitamin D deficiency was more prevalent in those with moderate COPD (FEV/FVC <70% and FEV1 50 to <80%; FEV1, forced expiratory volume in 1 s and FVC, forced vital capacity) and severe COPD (FEV/FVC <70% and FEV1 <50%) but not in those with mild COPD (FEV/FVC <70% and FEV1 >80%) or restrictive lung disease (FEV1/FVC >70% and FVC <80%) compared with men with normal lung function . Vitamin D deficiency was associated with increased risk of total and respiratory mortality in both men with COPD and men with restrictive lung disease after adjustment for confounders and inflammation. The adjusted HRs (95% CI) for total mortality comparing levels of 25(OH)D<10 ng/mL to 25(OH)D>=20 ng/mL were 1.39 (1.10 to 1.75), 1.52 (1.17 to 1.98), 1.58 (1.17 to 2.14) and 1.39 (0.83 to 2.33) for those with no lung impairment, restrictive lung function, mild/moderate COPD and severe COPD, respectively.Conclusion Men with COPD were more likely to be vitamin D deficient than those with normal lung function. Vitamin D deficiency is associated with increased all-cause mortality in older men with no lung impairment as well as in those with restrictive or obstructive lung impairment.